Evaluation the Role of Clinical Pharmacist on Prevents or Reduced the Medication Error in Emergency Department - bahaa, Rana; Al_Sabagh, may; Abbas, hassan (Iraqi National Journal of Nursing Specialties, 2013)
Objective: To identify the role and importance of the clinical pharmacist in the Emergency Department on preventor reduced the medication error.Methodology: We collected the medical file of 3400 patients, 1400 patient's file in (A) hospital, and 1000 patient'sfile in each of (B and C) hospital, who admitted to the ED, at primary weekdays between 8 am to 2 pm, andrecorded all the intervention made by clinical pharmacist through an active search in clinical charts, with analysisof the daily medical prescription. The potential severity of harm of the medication error judged by two reviewers,a permanent emergency physician, and clinical pharmacist based on the National Coordinating Council (NCC) ofMedication Error Reporting and Prevention error classification system.Results: Four of intervention that have the greatest incidence which represent the majority of the cases, and theywere related to: dosage 500 (38.7%), route of administration 300 (23.2%), frequency 100 (7.7%), andincompatibility 120 (9.3%). The severity of medication errors that was judged as potentially life threatening (67;5.1%), serious (135; 10.4%), significant (634; 49.1%), and insignificant (454; 35.1%). The acceptance to thepresence and intervention of pharmacist was as follow: senior physicians 75%, permanent physicians 20%, residentphysicians 77%, and nurses 30%.Recommendation: Hospitals should contemplate assigning well-trained knowledgeable, efficient and skilled EDclinical pharmacists to prospectively review medication orders whenever clinically possible. It is also recommendedthat each hospital performs acquainted analysis of medication errors occurring in its ED, in order to determinetheir origin and then establish the necessary ED-based clinical pharmacy services. The sets of actions needed toprovide such services, as well as the skills, which their ED pharmacists must possess or acquire in order to becapable of producing desired outcomes